Parental fecundability and neurodevelopmental delays and difficulties in offspring. (10th May 2022) - Magnus, Maria C; Havdahl, Alexandra; Wilcox, Allen J; Goisis, Alice
Abstract: Background: Impaired neurodevelopment is reported among children conceived by assisted reproductive technologies (ART). However, this might be explained by conditions underlying parental subfecundity, rather than the ART procedure. Methods: We examined associations of parental time-to-pregnancy (TTP) and conception by ART with neurodevelopmental traits up to 8 years of age, including motor and language skills, social delays and difficulties, and inattention-hyperactivity, among 92 142 singletons participating in the Norwegian Mother, Father and Child Cohort Study (MoBa). Mothers reported TTP and neurodevelopmental traits through questionnaires. Mean differences in standardized neurodevelopmental traits were estimated using linear regression, adjusting for maternal age, parity, educational level, body mass index and smoking, and paternal age. Results: A longer TTP was associated with decreased language skills and motor skills at 6, 18 and 36 months ( P -values for trend ≤0.01), prosocial skills delay at 36 months ( P -values for trend ≤0.001) and increased scores for inattention-hyperactivity traits at all ages up to 8 years ( P -values for trend from 0.06 to 0.01). Effect sizes were small, ranging between 0.03 and 0.05 difference in the standardized neurodevelopmental scores. Estimates for ART were imprecise, but there were no differences between children conceived by ART and naturally conceived children of subfecund parents (TTP ≥12 months). Conclusions: Longer parental TTP is modestly but robustly associated with offspring neurodevelopmental delays and difficulties, with no added impact of ART. Future studies should investigate the underlying causes of—or aspects related to—parental subfecundity which might explain the association with offspring neurodevelopmental delays and difficulties.